Illegal wildlife trade: a study of law on wildlife trade for consumption as exotic food and medicinal purposes in Malaysia in comparison with Thailand and Singapore. / Pairus Samsudin, Stephanie Sophia Mengan Ubun and Syarifah Fatimah Azura Wan Ali - Samsudin, Pairus; Mengan Ubun, Stephanie Sophia; Wan Ali, Syarifah Fatimah Azura (2007)
This research attempts to identify law on wildlife trade in the three selected countries. The focus of this research is on illegal wildlife trade for consumption and medicinal purposes. Information used in this research was mostly gathered from internet, books, interviews and seminar. In this research, comparison of laws of the three countries was made to highlight the effects of similarities and differences. Other than that, the offences stipulated in statute in these three countries are quite similar. Generally, the offences are unlawful purchasing, selling, possessing, hunting, killing, import, export, capturing and others. This research concludes that there are loopholes in the law in those countries in relation to protection of wildlife against illegal wildlife trade for the consumption as exotic food and medicinal purposes as there is no specific provision had been inserted to make such act as an offence under the law.